Religia a rozum w świetle filozofii Gianniego Vattimo - Torzewski, Antoni (Humaniora. Czasopismo Internetowe, 2019)
The reason’s emancipation ideal present in the Enlightenment is, according to Gianni Vattimo, convergent with a part of the history of the presence of religion in philosophical reflection. However regress of religious thought along with growth of the ”power” of reason ended because of self-abolition of reason in its emancipation. Thus religion returned to the philosophical thought and is broadly considered. Of course it is not the same religion but different – separated from classic metaphysics. For religion appears as a discourse focused not on reason, and at the same time not claiming the right to be a mirror of the absolute truth, but as focused on interpretation and secularization. In accordance with Vattimo’s thought, I will try to show, what abandonment of metaphysics is about and if it is also an abandonment of reason. Furthermore I will present the contemporary place of hermeneutical reflection on religion.